Semantic Validation of Standard-based Electronic Health Record Documents with W3C XML Schema - Rinner, C.; Janzek-Hawlat, S.; Sibinovic, S.; Duftschmid, G. (Methods of Information in Medicine, 2010)
Objectives: The goal of this article is to examine whether W3C XML Schema provides a practicable solution for the semantic validation of standard-based electronic health record (EHR) documents. With semantic validation we mean that the EHR documents are checked for conformance with the underlying archetypes and reference model.Methods: We describe an approach that allows XML Schemas to be derived from archetypes based on a specific naming convention. The archetype constraints are augmented with additional components of the reference model within the XML Schema representation. A copy of the EHR document that is transformed according to the before-mentioned naming convention is used for the actual validation against the XML Schema.Results: We tested our approach by semantically validating EHR documents conformant to three different ISO/EN 13606 archetypes respective to three sections of the CDA implementation guide “Continuity of Care Document (CCD)” and an implementation guide for diabetes therapy data. We further developed a tool to automate the different steps of our semantic validation approach.Conclusions: For two particular kinds of archetype prescriptions, individual transformations are required for the corresponding EHR documents. Otherwise, a fully generic validation is possible. In general, we consider W3C XML Schema as a practicable solution for the semantic validation of standard-based EHR documents.
Keywords: Medical records; computerized medical records system; reference standards